Bungei Kurabu (Hakubunkan, 1895)
Bungei Kurabu (Literary Club) was published by Hakubunkan publishing house from January 1895 to January 1933. The total number of volumes included 457 issues and 150 regular and irregular extra issues. Of these the 284 issues made available here are those released during the period running from 1895 to 1912. This magazine received the full support of its readership and became the major literary journal during the period it was in print. These magazines contain many valuable photographs of geigi (geisha/geiko), actors and entertainers, along with articles commenting on the trends and mores current at the time. This collection of primary sources will prove instrumental for research in modern literature as well as the study of art, theater, rakugo, social customs and many other areas significant for the understanding of modern Japan.(Cited description: NetAdvance Inc., Tokyo, Japan). - JapanKnowledge provides full PDF scans of Bungei Kurabu as a part of the
Coverage 1895-1912
Keywords: scanned original; Zeitschrift; Newspapers & Magazines; A14 Literature